Rancang Bangun Jaringan Wireless Menggunakan Mikrotik Captive Portal Di Smp Al Falah Assalam Sidoarjo - Muhammad Harist Murdani; Surya Priyambudi; Suzana Dewi (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
As per customary in Indonesia, most of Middle School doesn't have special personel for Information Technology, especially on Internet using Wireless Network Management. Even though Indonesian Govenrments policy clearly inclined to using Internet for supporting teaching and learning activities in school. UNBK (Ujian Nasional Berbasis Komputer) indirectly forcing school to provide a fullset computer laboratory which connected to World Wide Web using Internet connection. Thus, the Internet connection can only be used by student and teacher inside computer laboratory only, there are no wireless internet connection that can be used in classroom. Our purpose in this PPM is to provide design and implementation for wireless network topology using Mikrotik Router RB450 and TPLink Access Point to maximized Internet connection usage in several classroom which aren't connected yet.